Efficiency improvement of vertical axis water turbines using hydrofoils (2022)
Lately, the use of Computational Fluid Dynamics (CFD) to solve real-world problems involving energy production has increased substantially. The application of this technique in the study of hydrokinetic turbines can be oriented towards improving the efficiency of these mechanisms to increase the use of renewable energies. The use of Overset Meshing techniques is starting to be the norm for CFD simulation of these devices as it has increased the reliability and reduced the computational resources needed to optimize these devices. The present study, using overset meshing, looks to compare different blade profiles for a hydrokinetic turbine that could potentially be implemented near rivers that are not connected to the Colombian electrical grid. The GOE222, NACA0018, and E817 are analysed, and it is determined that for low TSR values the ideal blade is the NACA0018, while at higher TSR the E817 outperforms the other two. While the study realized is an extensive further analysis involving cavitation and experimental results are required to fully understand the behaviour of the turbine with the three different blades.